Cohort at Risk: Long-Term Consequences of Conflict for Child School Achievement - Hendrik Jürges; Luca Stella; Sameh Hallaq; Alexandra Schwarz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We investigate the long-term effect of households' exposure to the Israeli-Palestinian conflict during the Second Intifada (2000-2005) on children's primary school achievement in the West Bank. Our identification strategy exploits the exogenous geographical variation in locality-level conflict intensity. We show that an increase in family experience of conflict has a negative long-term effect on the educational attainment of children, and that impaired non-cognitive skills are likely channels.
Keywords: D10; I20; F51; O12; 330